Alterations in the body balance after two types of high intensity exercises - Gassi, E.; Bankoff, A.; Zamai, C.; Bekendorf, R.; Okano, A.; Moraes, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The aim this study went compare the alterations in body balance after fatiguing exercise performed on a tredmill and resistance exercise of the plantarflexor muscles. The results indicate that postural control in quiet standing can be maintained by compensatory mechanisms activated during muscle fatigue. Though, the largest alterations were found in antero posterior axis, and significant differences among the exercises were verified for the bipodalic and no dominant leg with eyes closed conditions. The bipodalic condition (with exception of the alterations after the tredmill test in the condition of the closed eyes) also presented a larger variation than the monopodalic condition.